Pengaruh Aplikasi Rizobakteri dan Pupuk Fosfat terhadap Produktivitas dan Mutu Fisiologis Benih Jagung Hibrida - Hipi, Awaludin; Surahman, Memen; Ilyas, Satriyas; Giyanto, Giyanto (Jurnal Penelitian Pertanian Tanaman Pangan, 2013)
Maize productivity could be improved by using good quality of seed of high yielding hybrid varieties. The objective of this research was to study the effect of rhizobacteria and P fertilizer on physiological quality of maize hybrid seed and maize productivity. The experiment was conducted at Lembar Village, West Lombok District, West Nusa Tenggara Province and at Seed Science and Technology Laboratory IPB from April to December 2012. The experiment was arranged in a split plot design with three replications. The main plot was P fertilizer (untreated, 50 kg, 100 kg, 150 kg, and 200 kg SP36/ha), and the subplot was rhizobacteria treatments (untreated, rhizobacteria B42, and rhizobacteria ATS4). The results showed that application of 100 kg SP36/ha increased maize yield compared to that of unfertilized. Rizhobacteria ATS4 increased plant height and productivity of maize. Application of ATS4 rhizobacteria followed by 100 kg SP36/ha fertilizer increased the percentage of good quality seeds. Application of rhizobacteria could reduce the use of SP36 fertilizer up 50% of the recommended rate. Rizobakteri ATS4 and fertilizer P 100 kg SP36/ha increased the physiological quality of harvested seeds after four month storage at 21-25oC temperature and 53-62% relatif humidity.